Scrutinizing the simultaneous impact of drought on irrigated agriculture and groundwater resources - Payab, Ahmad Haseeb; Banihabib, Mohammad Ebrahim; Turker, Umut (Elsevier Science Inc, 2020)
This study investigated and quantified the temporal and spatial effects of drought on selected irrigated crops and groundwater of a coastal aquifer (Guzelyurt/Morphou aquifer) in North Cyprus. Coupled reconnaissance drought index (RDI) and crop water and irrigation requirements program of Food Agricultural Organization (CROPWAT) simulation model is employed to quantitatively evaluate the impact of drought on irrigation water requirement (IWR) of citrus and pomegranate in different regions based on moderate, severe and extreme drought categories. The response of groundwater to drought effect is investigated by analyzing the historical groundwater level (GWL) data series with the standardized precipitation index (SPI) and RDI severity values and the trend is examined using parametric and non-parametric statistical tests. During moderate, severe, and extreme drought it is found that the increase in IWR of irrigated crops is 8%, 11%, and 16%, respectively. Overall, the mean increase in IWR during dry years of drought is approximately 12%. In general, the temporal rise and fall of GWLs of Guzelyurt/Morphou aquifer are closely related to the positive and negative values of SPI and RDI with a mean correlation coefficient of 0.173 and 0.170, respectively. These findings can be effective in strategizing sustainable plans against climate change for integrated management of irrigated agriculture and groundwater resources.
2nd International Conference on Water Problems in the Mediterranean Countries (WPMC) -- MAY 06-10, 2019 -- Near E Univ, Lefkosa, CYPRUS
Keywords: Drought; Groundwater; Irrigated agriculture; North Cyprus; RDI; SPI